La necesaria adaptación de las estructuras de representación en la empresa - Quintanilla Navarro, Beatriz (Cuadernos de Relaciones Laborales, 2008)
This research offers a series of reflections around the necessity to adapt the representation structures in a company, not only by discussing if such an adaptation is required or appropriate, but by facing the effective transformations that are taking place. These transformations are outlined by, at least, three parameters: — The company or work center, which is crucial to identify since it is the space in which the representation is articulated. — The number of workers and, with it, their identification as such “for representation purposes”. The obligations, in one case, and the possibility, in the other, to articulate the representation ways mentioned before, depend on these clarifications. — In order to defend and represent the collective interest, the mentioned formulas are regulated and protected. The investigation goes over the main aspects where these transformation processes are being registered, taking into consideration the Spanish and European Legal Ordinance.